2005
DOI: 10.1161/01.str.0000178543.19433.20
|View full text |Cite
|
Sign up to set email alerts
|

3D Ultrasound Measurement of Change in Carotid Plaque Volume

Abstract: Background and Purpose-New therapies are being developed that are antiatherosclerotic but that lack intermediate end points, such as changes in plasma lipids, which can be measured to test efficacy. To study such treatments, it will be necessary to directly measure changes in atherosclerosis. The study was designed to determine sample sizes needed to detect effects of treatment using 3D ultrasound (US) measurement of carotid plaque. Methods-In 38 patients with carotid stenosis Ͼ60%, ageϮSD 69.42Ϯ7.87 years, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
160
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(169 citation statements)
references
References 30 publications
4
160
1
4
Order By: Relevance
“…Carotid artery plaques have been previously reported to show reduction within 3 months. 26) We speculate that the pleiotropic effect may appear in parallel with the lipidlowering effect, which has been shown previously and in our study to be apparent within 3 months. According to this hypothesis, strong statins may have greater effects on atheromas; however, we were unable to detect the significant difference between strong and mild statins in our small series.…”
Section: Discussionsupporting
confidence: 84%
“…Carotid artery plaques have been previously reported to show reduction within 3 months. 26) We speculate that the pleiotropic effect may appear in parallel with the lipidlowering effect, which has been shown previously and in our study to be apparent within 3 months. According to this hypothesis, strong statins may have greater effects on atheromas; however, we were unable to detect the significant difference between strong and mild statins in our small series.…”
Section: Discussionsupporting
confidence: 84%
“…Using carotid intimal medial thickness measurements as a surrogate efficacy end-point, Bots et al reported that 468 patients would be required to detect a treatment effect of 30% (power 0.80) (33). Three-dimensional ultrasound of plaque in the carotids would require fewer patients to demonstrate efficacy, yet a recent study reported that 203 patients would still be needed to detect a 10% change in plaque volume (power = 0.90) measured over a three month period (34). Measuring the progression of coronary calcium with cardiac computed tomography has been proposed as yet another noninvasive alternative to evaluating disease progression, yet sample sizes required for these studies remain large, and there is the strong suggestion that calcification represents a fundamentally distinct biological process which may correlate less with clinical events than plaque volume progression (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Further- Abbreviations: MaxMaxPS, mean of the single maximum plaque score of each of the 12 carotid segments (range 0-3) at duplicate examinations; PS, plaque score more, it is important to mention that our plaque score is a categorical variable which may be less powerful to track changes in plaque burden over time than a continuous measure. Continuous plaque measures, such as the carotid plaque area, carotid plaque volume or vessel wall value, might therefore be more efficient in terms of sample size and duration of follow-up to measure changes 31,32) ; however, continuous plaque measures are much more expensive and time-consuming, which limits their extensive use. Additionally, we were able to track changes in atherosclerotic plaque burden over time despite this limitation.…”
Section: Discussionmentioning
confidence: 99%